Earnings management, leverage and earnings quality of manufacturing companies in Indonesia - Teguh Erawati; Rifka Tunnajiha (Proceeding International Conference on Accounting and Finance, 2023)
Problems with the reliability of earnings information often occur in Indonesia, thereby reducing investor confidence in earnings quality. This study aims to test and prove the effect of earnings management and leverage on earnings quality. This research is quantitative with secondary data. The sample used in this study consisted of 78 manufacturing companies isted on the Indonesian (2018-2021) Stock Exchange using a purposive sampling technique. The data analysis technique used is descriptive statistical test, classical assumption test and hypothesis testing which consists of t test, f test, multiple linear regression analysis test, and the coefficient of determination test the results of this study indicate that earnings management has a negative and significant effect on earnings quality, the higher the earnings management performed in a company, the lower the earnings quality. Leverage has a negative and significant effect on earnings quality. This shows that the higher the level of leverage, the lower the quality of the profits generated. Theoretical and practical findings in this study find theoretical implications that these findings expand theories about lava management and leverage in a company and the results of this study can strengthen in practice for manufacturing companies to be able to increase profits stably in each period, improve performance its finances, making strategies, and this research can also be used as material for consideration for entities and institutions to improve their organizational performance systems.